A novel numerical method coupling CFD with PSO vs. a mathematical approach in the modeling of photocatalytic degradation of NO - Zhang, Guoqing; Liu, Jiayou; Jia, Liuhu; Wang, Haiming; Tan, Zhongchao; Yu, Hesheng (Reaction chemistry & engineering, 2023)
This work develops a mathematical and a numerical model based on Langmuir–Hinshelwood kinetics and mass transfer theory for photocatalytic NO removal. The mathematical model employs the resistance-in-series theory, whereas the numerical one uses multiphysics computational fluid dynamics (CFD) simulation in conjunction with the particle swarm optimization (PSO) algorithm. For the first time, the CFD–PSO coupling method is used for optimizing the intrinsic kinetic parameters. Both models have been validated by experimental data . Specifically, the mathematical and numerical models can predict 80% and 96% of experimental data within a 5% relative error, respectively. The results emphasize the reliability of the CFD–PSO coupling method. Afterwards, the validated mathematical model quantifies the relative contributions of surface reaction and mass transfer to photodegradation, and the verified numerical model provides more reactor local details. The proposed models provide practical tools for modeling, design and optimization of photocatalytic reactors for environmental remediation.